Open Coding Descriptions - Barney G. Glaser (Grounded Theory Review: An International Journal, 2016)
Open coding is a big source of descriptions that must be managed and controlled when doing GT research. The goal of generating a GT is to generate an emergent set of concepts and their properties that fit and work with relevancy to be integrated into a theory. To achieve this goal, the researcher begins his research with open coding, that is coding all his data in every possible way. The consequence of this open coding is a multitude of descriptions for possible concepts that often do not fit in the emerging theory. Thus in this case the researcher ends up with many irrelevant descriptions for concepts that do not apply. To dwell on descriptions for inapplicable concepts ruins the GT theory as it starts. It is hard to stop. Confusion easily sets in. Switching the study to a QDA is a simple rescue. Rigorous focusing on emerging concepts is vital before being lost in open coding descriptions. It is important, no matter how interesting the description may become. Once a core is possible, selective coding can start which will help control against being lost in multiple descriptions.